The Association of Paternal Race and Ethnicity with Adverse Pregnancy Outcomes in a Contemporary U.S. Cohort - Palatnik, Anna; Garacci, Emma; Walker, Rebekah J.; Ozieh, Mukoso N.; Williams, Joni S.; Egede, Leonard E. (American Journal of Perinatology, 2019)
Objective Maternal racial and ethnic disparities exist in obstetric outcomes. The contribution of paternal race and ethnicity toward obstetric outcomes has been less well documented. The objective of this study was to investigate the association between paternal race and ethnicity and several adverse pregnancy outcomes.Study Design This was a retrospective cohort of birth data from the CDC National Vital Statistics, years 2013—2017. All singleton live births were included in the analysis. Records with missing paternal race and ethnicity were excluded. The primary dependent variables were the following adverse maternal and perinatal outcomes: gestational diabetes, hypertensive disorder of pregnancy, preterm birth <37 weeks, cesarean delivery, low birth weight <2,500 g, 5-minute Apgar's score <7, admission to neonatal intensive care unit (NICU), and assisted ventilation at > 6 hours of life. The main exposure was paternal race and ethnicity, which was grouped into non-Hispanic white, non-Hispanic black, Hispanic, and other. Other race and ethnicity category included: American Indian, Alaskan Native, Asian, Native Hawaiian, or other Pacific Islander. Univariable and multivariable analyses were done to determine whether paternal race and ethnicity was independently associated with adverse pregnancy outcomes.Results A total of 16,482,745 births were included. In univariable analysis, all adverse obstetric outcomes were significantly associated with paternal race and ethnicity. In multivariable analysis, controlling for maternal and paternal demographic characteristics and maternal clinical factors, paternal race and ethnicity remained significantly associated with the majority of the adverse pregnancy outcomes. The strongest association was seen with: (1) paternal non-Hispanic black race and ethnicity, and higher rates of LBW and preterm birth (Odds ratio [OR] = 1.25, 95% CI: 1.24–1.27 and OR = 1.14, 95% CI: 1.13–1.15, respectively); (2) paternal Hispanic race and ethnicity and lower rates of 5-minute Apgar's score <7, and assisted ventilation at >6 hours of life (OR = 0.78, 95% CI: 0.77–0.79, and OR = 0.77, 95% CI: 0.75–0.78, respectively); and (3) other paternal race and ethnicity and higher rates of gestational diabetes, but lower rates of hypertensive disorder of pregnancy and assisted ventilation >6 hours of life (OR = 1.26, 95% CI: 1.25–1.27; OR = 0.79, 95% CI: 0.78–0.80; and OR = 0.80, 95% CI: 0.78–0.82, respectively). All associations were in comparison to paternal non-Hispanic white race and ethnicity.Conclusion Paternal race and ethnicity has an independent association with adverse obstetric outcomes. The pathway and the extent of the paternal racial influence are not fully understood and deserve additional research.
Keywords: paternal race; paternal ethnicity; adverse pregnancy outcomes; maternal race; maternal ethnicity